Pemenuhan Kebutuhan Informasi pada TikTok: Studi Uses and Gratification di Era Digital - Adistri, Nabila; Rusman, Almira Adani; Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
This study examines the application of the Uses and Gratifications Theory (UGT) in understanding TikTok users' information needs in the digital era. Utilizing a qualitative approach through in-depth interviews, it explores the motivations, experiences, and perceptions of active TikTok users, predominantly digital natives. The findings reveal that TikTok effectively satisfies user information needs via intelligent algorithms delivering hyper-personalized content. Entertainment, education, and social interaction emerge as primary motivations for TikTok usage. Moreover, the platform offers practical value, such as skill tutorials, lifestyle inspiration, and product reviews tailored to individual needs. However, challenges such as questionable information validity and irrelevant content persist.  This research reinforces UGT by uncovering the complex dimensions of digital media use, encompassing psychological, cognitive, and social interactions. TikTok functions beyond a mere information channel, evolving into a dynamic digital space where knowledge, identity, and technology interact continuously. The study also highlights the role of TikTok as both an educational and entertainment platform, capable of providing solutions to everyday problems while fostering social connections. The implications extend to enhancing UGT by showcasing how modern media address multifaceted user needs. Recommendations include improving content validation mechanisms to increase credibility. This research offers valuable insights into how social media platforms like TikTok can adapt to evolving user demands, ensuring relevance and utility in the digital landscape.